(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
Based on the Speech given at David Held’s Funeral, West London Synagogue, Golders Green Cemetery, 18 March 2019. David Held, born in London, 27 August 1951 – died in Durham, 2 March 2019